A microcrystal-modified ZrB2-MoSi2 coating and preparation method thereof

By adding microcrystalline glass to the ZrB2-MoSi2 coating and using microcrystalline modification technology, the problem of loose and porous coating during oxidation at high temperatures is solved, efficient improvement of oxidation resistance and simplification of the preparation process is achieved, and oxygen resistance needs in ultra-high temperature environments are met.

CN119751078APending Publication Date: 2025-04-04HENAN ACAD OF SCI CARBON MATRIX COMPOSITES RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411943054.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing ZrB2-MoSi2 coating has loose and porous problems during the oxidation process at high temperatures, resulting in insufficient oxidation resistance, complex preparation process and large energy consumption, making it difficult to meet the oxygen barrier requirements in ultra-high temperature environments.

Method used

By using microcrystalline modification technology, by adding 5 wt.% to 15 wt.% of microcrystalline glass to the ZrB2-MoSi2 coating, microcrystalline assisted densification and in-situ modification, the sintering temperature is reduced, the preparation process is simplified, and the structural oxygen resistance capacity of the coating is improved.

Benefits of technology

It effectively reduces the density temperature of the coating, simplifies the preparation process, improves the oxidation resistance of the coating, enhances the comprehensive oxygen resistance capacity in ultra-high temperature environments, and saves energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751078A_ABST
    Figure CN119751078A_ABST
Patent Text Reader

Abstract

The invention relates to a microcrystal-modified ZrB2-MoSi2 coating and a preparation method thereof. The coating composition ratio is: ZrB2-MoSi2-5wt.% microcrystal glass to ZrB2-MoSi2-15wt.% microcrystal glass. The preparation method comprises preparing ZrB2-MoSi2 powder by a self-propagating combustion synthesis method, microcrystal modification, and densification sintering. The invention overcomes the problems of deterioration of structural oxygen barrier performance due to micropores and cracks in the existing ZrB2-MoSi2 coating preparation method, and has the advantages of in-situ modification of micropores and cracks, and lowering the densification temperature of the coating to a certain extent, thereby achieving the effect of energy saving and energy saving and emission reduction, and can effectively improve the comprehensive antioxidant capacity of the coating in an ultra-high temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of C / C composite materials, in particular to a microcrystal-modified ZrB2-MoSi2 coating and a preparation method thereof. Background Art

[0002] As an indispensable structural material in the defense and civilian fields, carbon structural materials are widely used in high-temperature aerospace components due to their low density, high specific strength, excellent mechanical properties, and good thermal shock resistance. However, the easy oxidation of carbon structural materials above 400°C seriously restricts their application. Therefore, coating technology has become a feasible option to improve the high-temperature performance of carbon structural materials.

[0003] In recent years, in the field of oxidation-resistant coatings, ZrB2-based systems have been widely studied due to their high melting point, low density, high thermal conductivity and high strength at ultra-high temperatures. However, ZrB2 will also become loose and porous during high-temperature oxidation. In order to suppress this defect, MoSi2 sintering additives are usually used to increase the compactness of ZrB2. SiO2, one of the oxidation products of MoSi2, has fluidity at high temperatures and can play a role in filling cracks and holes. At the same time, SiO2 can prevent oxygen from diffusing into the matrix and use the excellent film-forming ability of MoSi2 to reduce the oxidation consumption of ZrB2, thereby showing excellent high-temperature oxidation resistance. Therefore, ZrB2-MoSi2 system ceramic coatings have great potential in high-temperature oxidation resistance.

[0004] At present, ZrB2-MoSi2 ceramic coatings are mostly prepared by embedding method, but the required temperature is high and the efficiency is low. Zeng Yi et al. (Zeng Yi, Zhang Wuzhuang, Xiong Xiang. Antioxidation mechanism of SiC / ZrB2-MoSi2 composite coating on C / C composite material [J]. Journal of Composite Materials, 2010, 27(03): 50-55) prepared SiC / ZrB2-MoSi2 composite coating on the surface of C / C composite material by embedding method. It is necessary to prepare SiC transition layer at 1800℃ in advance and embed and sinter ZrB2-MoSi2 ceramic layer at 1500℃. However, the embedding process is complicated, the thickness of the prepared coating is unstable, and the required temperature is high. Zhang Yudong (Zhang Yudong, Li Jiwen, Wang Nannan, et al. Effect of SPS process parameters on the microstructure and high-temperature oxidation resistance of ZrB2-MoSi2-SiC composite ceramics [J]. Powder Metallurgy Materials Science and Engineering, 2020, 25(06): 505-512) et al. prepared ZrB2-MoSi2-SiC composite ceramics at 1700-2000℃ sintering temperature by spark plasma (SPS) method. Although the SPS method simplifies the preparation process, it requires high temperature and large energy, which is not conducive to energy conservation and emission reduction. Despite this, at present, ZrB2-MoSi2 coatings are mostly in service at temperatures above 1500℃. However, with the development of science and technology and the increasingly urgent demand for ultra-high temperature protection, the oxidation resistance at 1500℃ can no longer meet the current needs. It is necessary to further improve the oxidation resistance of ceramic coatings at ultra-high temperatures to meet the ultra-high temperature oxygen barrier needs at 1700℃. Zhang et al. (ZHANGM, RENX, ZHANGM, et al. Preparation of ZrB2–MoSi2 high oxygen resistant coating using nonequilibrium state powders by self-propagating high-temperature synthesis [J]. Journal of Advanced Ceramics, 2021, 10(05): 1011-1024.) prepared a relatively excellent ZrB2-MoSi2 coating at 1500°C by adjusting the SPS process. However, the prepared coating is difficult to completely rely on its own structure to resist oxygen erosion during the structural oxygen barrier process, and its structural defects will provide a diffusion channel for oxygen during the structural oxygen barrier process, thereby destroying the oxygen barrier stability of the coating and weakening the comprehensive oxygen barrier capacity of the coating. A feasible method is urgently needed to solve the current problems of high preparation temperature, high energy consumption, preparation defects and improving the comprehensive oxygen barrier capacity of ultra-high temperature ceramic coatings. Summary of the invention

[0005] The present invention aims to provide a microcrystal-modified ZrB2-MoSi2 coating, which utilizes microcrystal-assisted densification to solve the drawbacks of the above-mentioned prior art.

[0006] To achieve the above purpose, the technical solution provided by the present invention is:

[0007] A microcrystal-modified ZrB2-MoSi2 coating, characterized in that the coating composition ratio is: ZrB2-MoSi2-5wt.% microcrystal glass to ZrB2-MoSi2-15wt.% microcrystal glass.

[0008] The present invention also discloses a method for preparing a microcrystalline modified ZrB2-MoSi2 coating, which is carried out according to the following steps:

[0009] (1) using zirconium powder, boron powder, molybdenum powder and silicon powder as raw materials, mixing the raw materials according to a molar ratio of 1:2:1:2, pressing the mixed powder into a block using a tablet press, placing the block into a self-propagating combustion synthesis furnace, and preparing ZrB2-MoSi2 powder using a self-propagating combustion synthesis method;

[0010] (2) uniformly mixing the ground ZrB2-MoSi2 powder with microcrystalline glass powder to obtain ZrB2-MoSi2-microcrystalline glass mixed powder;

[0011] (3) placing the ZrB2-MoSi2-glass-ceramics mixed powder into a graphite mold and placing a graphite matrix in the middle;

[0012] (4) placing the graphite mold in a spark plasma sintering furnace and evacuating the furnace to wait for densification sintering;

[0013] (5) starting the densification sintering process and cooling naturally to room temperature after the densification is completed;

[0014] (6) After sintering, the product in the furnace is taken out and polished to obtain a microcrystalline modified ZrB2-MoSi2 coating.

[0015] Preferably, in step (2), the mass ratio of the components in which the ZrB2-MoSi2 powder and the microcrystalline glass powder are uniformly mixed is in the range of 100:5 to 100:15.

[0016] Preferably, in step (5), the sintering parameters are: calcination temperature 1300-1380°C.

[0017] The advantages of the present invention compared with the prior art are:

[0018] 1. The present invention utilizes microcrystal-assisted densification, which not only retains the advantage of using spark plasma sintering to quickly achieve coating densification in a short time, ensuring the preparation cycle of coating samples, but also avoids the problem of large holes that may exist in the usual densification process; it also takes advantage of the use of microcrystals to assist in in-situ modification of the coating structure, thereby reducing the sintering temperature and achieving the effect of energy conservation and emission reduction.

[0019] 2. As an effective coating preparation method, the microcrystal-modified ZrB2-MoSi2 coating of the present invention utilizes microcrystal-assisted modification technology, which overcomes the problems of micropore defects and other problems existing in the coating densification process of the existing conventional plasma activation technology, and has the advantage of in-situ modification; it also overcomes the problems of high coating preparation temperature and complex process in the existing process, and has the advantages of reducing the densification temperature, simplifying the preparation difficulty, and saving energy consumption.

[0020] 3. By adopting this method, the densification temperature of the microcrystal-modified ZrB2-MoSi2 coating can be as low as 1300-1380°C, which is about 200°C lower than the densification temperature of the coating by conventional plasma activation technology, greatly saving production costs; and the in-situ modification effect of the microcrystal modification technology is utilized to effectively repair the micropores of the densified coating by the plasma activation technology, further improve the structural oxygen barrier capacity of the coating, reduce the loss of the coating during the film forming process, and enhance the comprehensive antioxidant capacity of the coating in ultra-high temperature environment.

[0021] In summary, the present invention overcomes the problems of the existing ZrB2-MoSi2 coating preparation method, such as the degradation of the structural oxygen barrier performance due to micropores and cracks. It has the advantages of in-situ modification of micropores and cracks and reducing the densification temperature of the coating to a certain extent, thereby achieving the effect of saving energy and reducing emissions, and can effectively improve the comprehensive antioxidant ability of the coating in ultra-high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a process flow chart of the present invention.

[0023] Figure 2 Schematic diagram of the microcrystal densification mechanism described in the present invention.

[0024] Figure 3 These are the X-ray diffraction phase analysis results of the microcrystal-modified ZrB2-MoSi2 coatings obtained in Examples 1 to 3 of the present invention and the conventional ZrB2-MoSi2 coating obtained in Comparative Example 1.

[0025] Figure 4 This is a scanning electron microscope morphology image of the microcrystalline modified ZrB2-MoSi2 coating obtained in Example 1 of the present invention.

[0026] Figure 5This is a scanning electron microscope morphology image of the microcrystal-modified ZrB2-MoSi2 coating obtained in Example 2 of the present invention.

[0027] Figure 6 This is a scanning electron microscope morphology image of the microcrystal-modified ZrB2-MoSi2 coating obtained in Example 3 of the present invention.

[0028] Figure 7 This is a scanning electron microscope morphology image of the conventional ZrB2-MoSi2 coating obtained in Comparative Example 1 of the present invention.

[0029] Figure 8 The graph of the oxidation weight gain per unit area of ​​Examples 1 to 3 of the present invention and the comparative example is shown.

[0030] Fig. 9 It is a graph of average protection efficiency of Examples 1 to 3 of the present invention and a comparative example. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0032] Embodiment 1:

[0033] This embodiment discloses a microcrystal-modified ZrB2-MoSi2 coating and a preparation method thereof, wherein the microcrystal-modified ZrB2-MoSi2 coating involved in this embodiment is a multiphase coating in which ZrB2-MoSi2 and microcrystalline glass coexist, and the composition ratio is: ZrB2-MoSi2-5wt.% microcrystalline glass (mass ratio), and the preparation method thereof is carried out according to the following steps:

[0034] (1) using zirconium powder, boron powder, molybdenum powder and silicon powder as raw materials, mixing the raw materials according to a molar ratio of 1:2:1:2, pressing the mixed powder into a block using a tablet press, placing the block into a self-propagating combustion synthesis furnace, and preparing ZrB2-MoSi2 powder using a self-propagating combustion synthesis method;

[0035] (2) uniformly mixing the ground ZrB2-MoSi2 powder and microcrystalline glass powder in a mass ratio of 100:5 to obtain ZrB2-MoSi2-microcrystalline glass mixed powder;

[0036] (3) placing the ZrB2-MoSi2-glass-ceramics mixed powder into a graphite mold and placing a graphite matrix in the middle;

[0037] (4) placing the graphite mold in a spark plasma sintering furnace and evacuating the furnace to wait for densification sintering;

[0038] (5) starting the densification sintering process at a sintering temperature of 1300°C and cooling naturally to room temperature after the densification is completed;

[0039] (6) After sintering, the product in the furnace is taken out and polished to obtain a microcrystalline modified ZrB2-MoSi2 coating.

[0040] The phase structure and micromorphology are as follows Figure 3 and Figure 4 As shown in Figure 2, the oxidation resistance at 1700℃ is as follows: Figure 8 , Fig. 9 And as shown in Table 1.

[0041] Embodiment 2:

[0042] This embodiment discloses a microcrystal-modified ZrB2-MoSi2 coating and a preparation method thereof, wherein the microcrystal-modified ZrB2-MoSi2 coating involved in this embodiment is a multiphase coating in which ZrB2-MoSi2 and microcrystalline glass coexist, and the composition ratio is: ZrB2-MoSi2-10wt.% microcrystalline glass (mass ratio), and the preparation method thereof is carried out according to the following steps:

[0043] (1) using zirconium powder, boron powder, molybdenum powder and silicon powder as raw materials, mixing the raw materials according to a molar ratio of 1:2:1:2, pressing the mixed powder into a block using a tablet press, placing the block into a self-propagating combustion synthesis furnace, and preparing ZrB2-MoSi2 powder using a self-propagating combustion synthesis method;

[0044] (2) uniformly mixing the ground ZrB2-MoSi2 powder and microcrystalline glass powder in a mass ratio of 100:10 to obtain ZrB2-MoSi2-microcrystalline glass mixed powder;

[0045] (3) placing the ZrB2-MoSi2-glass-ceramics mixed powder into a graphite mold and placing a graphite matrix in the middle;

[0046] (4) placing the graphite mold in a spark plasma sintering furnace and evacuating the furnace to wait for densification sintering;

[0047] (5) starting the densification sintering process at a sintering temperature of 1350°C and cooling naturally to room temperature after densification is completed;

[0048] (6) After sintering, the product in the furnace is taken out and polished to obtain a microcrystalline modified ZrB2-MoSi2 coating.

[0049] The phase structure and micromorphology are as follows Figure 3 and Figure 5 As shown in Figure 2, the oxidation resistance at 1700℃ is as follows: Figure 8 , Fig. 9 And as shown in Table 1.

[0050] Embodiment 3:

[0051] This embodiment discloses a microcrystal-modified ZrB2-MoSi2 coating and a preparation method thereof, wherein the microcrystal-modified ZrB2-MoSi2 coating involved in this embodiment is a multiphase coating in which ZrB2-MoSi2 and microcrystalline glass coexist, and the composition ratio is: ZrB2-MoSi2-15wt.% microcrystalline glass (mass ratio). The preparation method thereof is carried out according to the following steps:

[0052] (1) using zirconium powder, boron powder, molybdenum powder and silicon powder as raw materials, mixing the raw materials according to a molar ratio of 1:2:1:2, pressing the mixed powder into a block using a tablet press, placing the block into a self-propagating combustion synthesis furnace, and preparing ZrB2-MoSi2 powder using a self-propagating combustion synthesis method;

[0053] (2) uniformly mixing the ground ZrB2-MoSi2 powder and microcrystalline glass powder in a mass ratio of 100:15 to obtain ZrB2-MoSi2-microcrystalline glass mixed powder;

[0054] (3) placing the ZrB2-MoSi2-glass-ceramics mixed powder into a graphite mold and placing a graphite matrix in the middle;

[0055] (4) placing the graphite mold in a spark plasma sintering furnace and evacuating the furnace to wait for densification sintering;

[0056] (5) starting the densification sintering process at a sintering temperature of 1380°C and cooling naturally to room temperature after the densification is completed;

[0057] (6) After sintering, the product in the furnace is taken out and polished to obtain a microcrystalline modified ZrB2-MoSi2 coating.

[0058] The phase structure and micromorphology are as follows Figure 3 and Figure 6 As shown in Figure 2, the oxidation resistance at 1700℃ is as follows: Figure 8 , Fig. 9 And as shown in Table 1.

[0059] Comparative Example 1:

[0060] The ZrB2-MoSi2 coating involved in this comparative example is a ZrB2-MoSi2 coating without adding microcrystalline glass, and the composition ratio is: ZrB2-MoSi2-0wt.% microcrystalline glass (mass ratio), and the preparation method thereof is carried out according to the following steps:

[0061] (1) preparing ZrB2-MoSi2 powder by self-propagating combustion synthesis method according to the molar ratio;

[0062] (3) placing ZrB2-MoSi2 powder into a graphite mold and placing a graphite matrix in the middle;

[0063] (4) placing the graphite mold in a spark plasma sintering furnace and evacuating the furnace to wait for densification sintering;

[0064] (5) starting the densification sintering process at a sintering temperature of 1300°C and cooling naturally to room temperature after the densification is completed;

[0065] (6) After sintering, the product in the furnace is taken out and polished to obtain a ZrB2-MoSi2 coating.

[0066] The phase structure and micromorphology are as follows Figure 3 and Figure 7 As shown in Figure 2, the oxidation resistance at 1700℃ is as follows: Figure 8 , Fig. 9 And as shown in Table 1.

[0067] On the basis of Example 1, step (2) was removed, that is, no microcrystal modification treatment was performed, and step (3) was directly performed. The sample obtained in Comparative Example 1 had pores, and the structural oxygen barrier had many defects, which provided a channel for oxygen diffusion. In addition, the comprehensive oxygen barrier capacity of the coating was also very different. The oxidation weight gain of the sample without microcrystal modification treatment was significantly increased, and the oxidation protection efficiency was significantly reduced.

[0068] Table 1 Results of oxidation weight gain and oxidation protection efficiency at 1700℃

[0069] Oxidation weight gain / (10-2)g·cm-2 Protection efficiency / % Example 1 0.3275 99.82 Example 2 0.1744 99.96 Example 3 0.2369 99.90 Comparative Example 1 0.7398 99.57

[0070] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.

Claims

1. A microcrystalline modified ZrB2-MoSi2 coating, characterized in that: The coating composition ratio is: ZrB2-MoSi2-5wt.% microcrystalline glass to ZrB2-MoSi2-15wt.% microcrystalline glass.

2. A method for preparing a microcrystalline modified ZrB2-MoSi2 coating, characterized in that: Follow these steps: (1) using zirconium powder, boron powder, molybdenum powder and silicon powder as raw materials, mixing the raw materials according to a molar ratio of 1:2:1:2, pressing the mixed powder into a block using a tablet press, placing the block into a self-propagating combustion synthesis furnace, and preparing ZrB2-MoSi2 powder using a self-propagating combustion synthesis method; (2) uniformly mixing the ground ZrB2-MoSi2 powder with microcrystalline glass powder to obtain ZrB2-MoSi2-microcrystalline glass mixed powder; (3) placing the ZrB2-MoSi2-glass-ceramics mixed powder into a graphite mold and placing a graphite matrix in the middle; (4) placing the graphite mold in a spark plasma sintering furnace and evacuating the furnace to wait for densification sintering; (5) starting the densification sintering process and cooling naturally to room temperature after the densification is completed; (6) After sintering, the product in the furnace is taken out and polished to obtain a microcrystalline modified ZrB2-MoSi2 coating.

3. The method for preparing a microcrystalline modified ZrB2-MoSi2 coating according to claim 2, characterized in that: In step (2), the ZrB2-MoSi2 powder and the microcrystalline glass powder are uniformly mixed in a mass ratio ranging from 100:5 to 100:

15.

4. The method for preparing a microcrystalline modified ZrB2-MoSi2 coating according to claim 1, characterized in that: In step (5), the sintering parameters are: calcination temperature 1300-1380°C.